Microvesicle phenotypes are associated with transfusion requirements and mortality in subjects with severe injuries. Issue 1 (17th December 2015) - Matijevic, Nena; Wang, Yao‐Wei W.; Holcomb, John B.; Kozar, Rosemary; Cardenas, Jessica C.; Wade, Charles E.
Abstract : Background: Severe injury often results in substantial bleeding and mortality. Injury provokes cellular activation and release of extracellular vesicles. Circulating microvesicles (MVs) are predominantly platelet‐derived and highly procoagulant. They support hemostasis and vascular function. The roles of MVs in survival after severe injury are largely unknown. We hypothesized that altered MV phenotypes would be associated with transfusion requirements and poor outcomes. Methods: This single‐centre study was approved by the Institutional Review Board. The study cohort consisted of patients with major trauma requiring blood product transfusion and 26 healthy controls. Plasma samples for MVs were collected upon admission to the emergency department (n=169) and post‐resuscitation (n=42), and analysed by flow cytometry for MV counts and cellular origin: platelet (PMV), erythrocyte (RMV), leukocyte (LMV), endothelial (EMV), tissue factor (TFMV), and annexin V (AVMV). Twenty‐four hour mortality is the outcome measurement used to classify survivors versus non‐survivors. Data were compared over time and analysed with demographic and clinical data. Results: The median age was 34 (IQR 23, 51), 72% were male, Injury Severity Score was 29 (IQR 19, 36), and 24 h mortality was 13%. MV levels and phenotypes differed between patients and controls. Elevated admission EMVs were found both in survivors (409/µL) and non‐survivors (393/µL) compared to controls (23/µL, p<0.001) and persisted over time. Admission levels of PMV, AVMV, RMV, and TFMV were significantly lower in patients who died compared to survivors, but were not independently associated with the 24 h mortality rate. Patients with low MV levels at admission received the most blood products within the first 24 h. AVMV and PMV levels either increased over time or stabilized in survivors but decreased in non‐survivors, resulting in significantly lower levels at intensive care unit admission in non‐survivors (1, 048 vs. 1, 880 AVMV/µL, p<0.00004 and 1, 245 PMP/µL vs. 1, 866 PMP/µL, p=0.003). Conclusion: Severe injury results in endothelial activation and altered MV phenotypes. Significant differences in specific MV phenotypes or changes over time were associated with blood product requirements and the 24 h mortality rate.